Techniques Used by Students in Translating Report Text from Indonesian into English - Tasyakurna M, Annisa; Andhini, Aulia; Pratama, Eggi (English Education Journal, 2023)
Due to the different aspects of the source language and the target language, there are some techniques involved in the translation process to achieve the equivalence of the translation result. This study is aimed at analyzing the dominant translation techniques as proposed by Molina and Albir (2002) used by the third year students of the English Department in translating report text from Indonesian into English. Descriptive research was used to examine this research and also translation test and interview were used to collect research data online. The sample of this research was 36 students who learned translation study. There were several results that the researchers found while conducting the research. The results of this research that have obtained in this study were the most dominant technique used by students in translating report text was established equivalent.The function of this research is to give additional information to the readers about the techniques used in translating the texts.